1999
DOI: 10.1016/s0014-5793(99)01462-3
|View full text |Cite
|
Sign up to set email alerts
|

PiUS (Pi uptake stimulator) is an inositol hexakisphosphate kinase

Abstract: A cDNA cloned from its ability to stimulate inorganic phosphate uptake in Xenopus oocytes (phosphate uptake stimulator (PiUS)) shows significant similarity with inositol 1,4,5-trisphosphate 3-kinase. However, the expressed PiUS protein showed no detectable activity against inositol 1,4,5-trisphosphate, nor the 1,3,4,5-or 3,4,5,6-isomers of inositol tetrakisphosphate, whereas it was very active in converting inositol hexakisphosphate (InsP 6 ) to inositol heptakisphosphate (InsP 7 ). PiUS is a member of a famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
83
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(85 citation statements)
references
References 25 publications
1
83
1
Order By: Relevance
“…Earlier, we noted that IP 7 phosphorylation occurs primarily at stretches of serines flanked by acidic amino acids and concluded that phosphorylation occurs on the serine residues (18) (also see SI Fig. 6).…”
Section: Resultsmentioning
confidence: 72%
See 4 more Smart Citations
“…Earlier, we noted that IP 7 phosphorylation occurs primarily at stretches of serines flanked by acidic amino acids and concluded that phosphorylation occurs on the serine residues (18) (also see SI Fig. 6).…”
Section: Resultsmentioning
confidence: 72%
“…In our earlier study, we showed that 5␤[ 32 P]IP 7 phosphorylates a wide range of proteins in both the yeast, S. cerevisiae, and in mammalian tissues (18). We characterized in detail phosphorylation of several of these proteins, such as the yeast proteins NSR1 and SRP40.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations